(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The outbreak of poisoning often happens especially on the elementary school children. The case of poisoning might be happened to the students because they buy snacks which are expired or unhealthy. Theoritically, knowledge is a very important element which influencing someone’s behaviour. Selecting unhealthy snack might be caused by lack of knowledge about snack that can influence their snacking habit. The purposes of this study were: to describe student’s knowledge about snacks based on gender and availability of information that correlation with student’s knowledge about snacks, to describe family’s and school’s influences that corellation with student’s knowledge about snacks, to describe student’s snacking behaviour based on gender, and to analyze correlation between student’s knowledge about snacks and their snacking behaviour. This research was observasional on and conducted cross-sectionally. The data were primarily taken from interview supported by questioners and observation and secondary from interrelated institution (BPOM and literature). The population of this research were students of third, fourth and fifth grades from Kedurus IV elementary school, Karang Pilang subdistrict, Surabaya, school year 2004/ 2005, totally 136 students. Sample unit were students of third, fourth and fifth from this school, total 57 students who were chosen by Proportional Random Sampling method. The result of this study showed 56% of girls had good knowledge about snacks, 77% of students got information about snacks from television, 91% of students said that their parents gave information about snacks, 96% of students said that their teachers gave information about snacks, 67% of girls had good snacking behaviour. There was a correlation between student’s knowledge about snacks and student’s snacking behaviour by using chi square test p= 0.038. For increasing student’s knowledge, the students need more information about snacking behaviour and unhealthy snacks.